P‐170: Molecular Design of Sensitizer for High Efficiency in Hyper‐fluorescent Organic Light‐Emitting Diodes. Issue 1 (30th May 2018) - Jang, Ji Seon; Han, Si Hyun; Choi, Hye Won; Yook, Kyoung Soo; Lee, Jun Yeob
Abstract : We synthesized two thermally activated delayed fluorescent (TADF) emitters sensitizers, 9, 9′, 9″‐(5‐(4, 6‐diphenyl‐1, 3, 5‐triazin‐2‐yl)benzene‐1, 2, 3‐triyl)tris(3, 6‐dimethyl‐9H‐carbazole) (TmCzTrz) and 9, 9′, 9″‐(5‐(4, 6‐diphenyl‐1, 3, 5‐triazin‐2‐yl)benzene‐1, 2, 3‐triyl)tris(3, 6‐di‐tert‐butyl‐9H‐carbazole) (TbCzTrz) to investigate as the sensitizers in hyper‐fluorescent organic light emitting diodes (OLEDs). The difference in two TADF sensitizers was the side group that was consisted of methyl and t‐butyl group. Although the efficiency of TbCzTrz based TADF device was lower than that of the TmCzTrz device, the efficiency of the hyper‐fluorescent device using the as sensitizers was almost the same.